Life and Fertility. Moral Aspects of Natural Methods of Planning Family - Kluz, Marek (Studia Warmińskie, 2011)
Fertility is an inalienable feature of a human being, a fundamental function of sexuality, an attribute of maturity and an element that belongs to the essence of life. Fertility as an attribute of spousal love describes the field of many mutual achievements of a couple. Life processes are thus wisely regulated by nature itself in its biological rhythm. The knowledge of corporality and the rhythms of fertility is a prerequisite for responsible parenthood. Thus, responsible parenthood is an important matter for every married couple and the knowledge of nature is of much help in this area. To get to know nature better one must refer to the natural methods of conception, accepted and recommended by the Church. The aim of this publication is to present the natural methods of planning a family as an alternative to other methods widespread in the modern world which pose a danger to human life, marital bond and human dignity. Despite many publications which raise this issue, the subject of giving life in harmony with nature still remains open and inexhaustible.